2008
DOI: 10.1177/1059840508319627
|View full text |Cite
|
Sign up to set email alerts
|

The SunWise Policy Intervention for School-Based Sun Protection: A Pilot Study

Abstract: Skin cancer is highly preventable, but clearly there is a critical need to focus on better ways to disseminate information about known skin cancer prevention. The U.S. Environmental Protection Agency's (EPA) SunWise Program is one channel for reaching children, teachers, and school nurses. In a pilot study designed to increase adoption of school-based sun protection policies, 28 schools were randomly assigned to one of three groups: Control, which included the EPA's original SunWise curriculum toolkit; SunWise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
(20 reference statements)
1
17
0
1
Order By: Relevance
“…A number of studies [5,8,9,11,12] have attempted to change the sun protection behaviors of adolescents by offering sun safety education programs in schools. Most of the school-based interventions increase the sun protection knowledge, while only a limited number of interventions changed intended or actual behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies [5,8,9,11,12] have attempted to change the sun protection behaviors of adolescents by offering sun safety education programs in schools. Most of the school-based interventions increase the sun protection knowledge, while only a limited number of interventions changed intended or actual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. Centers for Disease Control and Prevention recommends school programs on sun safety. Some school-based sun safety education programs have been reported in many studies, such as the "SunSmart Schools" in Victorian primary schools and other Australian states [4], a sun safety education program for primary school students in Switzerland [5,6], raising sun protection and early detection awareness among Florida high schoolers [7], and the SunWise Program in the US [8]. In Arizona, skin cancer prevention in the class education activity program, "Students are Sun Safe," was delivered by university students for middle and high school students [9].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of the adolescents stated to have fewer than 10 moles in their bodies. In literature, it is reported that having light hair color, blue-green eye color and light skin color and the presence of multiple moles in body increase the risk for skin cancer (Baum and Cohen, 1998;Cokkinides et al, 2002;Emmons et al, 2008;Saridi et al, 2009). Our findings are similar to the results of the study performed by Uysal et al (2004) on 12-15 years of age students in Izmir reported that nearly 35% of students have light eye and skin color and also moles.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence is 0.6% in men and mortality rate is 0.4%, while these rates are 1.0% and 0.7% in women (Globocan 2008). There is a risk of skin cancer for everyone; however, people with light skin, multiple moles and stains, overexposure to sun and history of sunburn are under higher risk of skin cancer (Baum and Cohen 1998;Cokkinides et al, 2002;Emmons et al, 2008;Feher et al, 2010;Heckman and Coups 2011). Due to the strong relationship between sunburns in childhood and skin cancer, 80% of all skin cancer cases can be prevented with suitable protective measures (Boyett et al, 2002;Baz et al, 2003;Balk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…P: Sun exposure during childhood is a key contributor to the development of skin cancer [18][19][20][21] . Therefore, studies conducted with children in preschool education institutions constituted the target group of this study.…”
Section: Inclusion Criteriamentioning
confidence: 99%